The Learner's Engagement in the Learning Process Designed Based on the Experiential Learning Theory in Post Graduate Program at Open University Malaysia - Zahari Hamidon (Association for Computing Machinery, 2018)
Today, the methods of delivering knowledge through online have become diverse, and online learning environments have reached its maturity as evidenced by the fact that most institutions of higher learning are either using them or considering making them one of the leading modes of teaching and learning. Learners today are becoming open-minded due to the technology that provides communication channels with different features and functionality. This study aims to observe the learner's engagement in the learning process designed based on four modes of the Experiential Learning Theory (ELT) model. Based on a case study and literature review, this study seeks to determine the components of Experiential Learning Theory to be synthesised into the learning process to create an effective lesson design. This study will report on the effects of the lesson design synthesised from the Experiential Learning Theory that is translated into the learning process, from the 'grasp experience' phase to 'transform experience' phase in the ELT learning cycle. The analytic learning data from the report in Moodle based Learning Management System is used to measure the learner's engagement. (Abstract by author)